ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LIQUIDITY CREATION PERBAN K A N INDONESIA (Studi Kasus pada 10 Bank Terbesar di Indonesia pada Periode 2007 sampai dengan 2012) - Hestiyani, Medikatama; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2013)
Banking sector is the major financial institutions in economy. The main task of the bank is as intermediary, the intermediary function is an activity that raise funds from the public that haveexcess funds in the form of savings and distribute it to other people who needs it in the form called loans. This intermediation process create liquidity creation. This research is aimed to examin somefactor like Reserve Requirement (RR), bank capital ratio, bank risk (earning volatility, credit risk, distance to default), and bank size in influencing liquidity creation.The samples in this study are ten largest Indonesian banks in 2012. The sampling methodused is purposive sampling. The data Â used in this study is banks annual report from year 2007 until 2012. Data analysis method used is multiple linear regression. Hypothesis testing is done using t test and F test.The studies found that Reserve Requirement (RR), bank capital ratio, andearning volatility has negative effect on liquidity creation. While credi reisk, distance to default, and bank size haspositive effect on liquidity creation. The result of the regression show the predictive ability of six independent variables on liquidity creation is 38,9%, while the remaining 61,1% is influenced byother factors outside the model of this study